Sustainability, safety and security: A case for hospitality industry response to natural disasters / Veda Ward and Alex Mattern. - Ward, Veda; Mattern, Alex (Universiti Teknologi Mara Selangor, 2019)
Natural disasters are increasing around the world and at the same time the hospitality industry is poised for growth. Recent emphasis on standards for pre-professional education and high-quality industry experiences have attracted professionals to be committed to longer term careers in industry. The present study, informed by four theoretical frameworks, incorporates and tests the dynamic interaction among three of the drivers in hospitality, tourism, culinary and recreation career areas; sustainability, safety and security. A case study methodology was employed to examine a series of industry responses to a specific natural disaster. Responses by various industry sectors were reviewed. Recommendations are made for future research, human resources approaches, technological innovation and integration that allow the industry to become a key player in this context.